2002
DOI: 10.3171/jns.2002.96.2.0287
|View full text |Cite
|
Sign up to set email alerts
|

Brain edema after experimental intracerebral hemorrhage: role of hemoglobin degradation products

Abstract: Hemoglobin causes brain edema, at least in part, through its degradation products. Limiting hemoglobin degradation coupled with the use of iron chelators may be a novel therapeutic approach to limit brain edema after ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
315
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(338 citation statements)
references
References 53 publications
16
315
1
2
Order By: Relevance
“…The same authors found that subsequently heme‐oxygenase 1, an enzyme, degrading hemoglobin into carbon monoxide, biliverdin, and iron was markedly increased. Intracellular iron overload was shown to result in lipid peroxidation and free radical formation leading to delayed edema and acute brain injury 35, 36, 37, 38, 39. In accordance with these findings, brain tissue damage was reported to be reduced in experimental SAH by the knockout of lipocalin 2, an iron transport protein 40.…”
Section: Discussionmentioning
confidence: 53%
“…The same authors found that subsequently heme‐oxygenase 1, an enzyme, degrading hemoglobin into carbon monoxide, biliverdin, and iron was markedly increased. Intracellular iron overload was shown to result in lipid peroxidation and free radical formation leading to delayed edema and acute brain injury 35, 36, 37, 38, 39. In accordance with these findings, brain tissue damage was reported to be reduced in experimental SAH by the knockout of lipocalin 2, an iron transport protein 40.…”
Section: Discussionmentioning
confidence: 53%
“…For instance, patients with naturally high levels of macrophage/microglial CD163 may have faster rates of hematoma resorption, and/or less neuroinflammation due to rapid sequestration of toxic hemoglobin. In various experimental models of ICH, augmenting hematoma clearance or neutralizing hemoglobin toxicity generally result in less PHE, reduced tissue injury, and improved functional performance in the animals 4, 5, 25, 26…”
Section: Discussionmentioning
confidence: 99%
“…The initial tissue injury of ICH activates numerous secondary injury pathways, including the release of toxic hemolysis products, enhanced oxidative stress, and robust proinflammatory responses. On a macroscopic level, these processes can result in blood‐brain‐barrier (BBB) disruption, tissue shifts and perihematomal edema (PHE) formation that can result in further neurological deterioration 4, 5, 6. As these secondary injury pathways can evolve over hours to days, they represent attractive targets for medical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…There is overwhelming evidence in young and old animals from several species of the ability of iron chelator desferrioxamine to reduce neurologic injury and improve functional recovery following ICH Hua et al, 2006;Huang et al, 2002;Nakamura et al, 2004a;Okauchi et al, 2009;Song et al, 2007;Wan et al, 2006Wan et al, , 2009Wu et al, 2011b). This remains the most promising putative neuroprotectant, having advanced to clinical trials (Selim, 2009) with a phase II currently underway.…”
Section: Future Directionsmentioning
confidence: 99%